UNDERSTANDING LAW ENFORCEMENT IN THE PERSPECTIVE OF EXPEDIENCY AND JUSTICE - Yahman, Dr. Yahman (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2024)
The fundamental concept of law enforcement is to maintain order by maintaining the values of society with the norms outlined in the rule of law. This research aims to identify the rules and norms of law enforcement in Indonesia. This is normative juridical research combined with statutory and conceptual approaches. Based on the research results, it is concluded that from the subject perspective, law enforcement is defined as a particular law enforcement institution’s attempt to assure and ascertain that legal rules are implemented properly. Meanwhile, in terms of its object, law enforcement concerns the enforcement of formal written regulations. Furthermore, in implementing their tasks and authorities, legal authorities not only use certainty, but also equity and utility. In the perspective of the expediency approach, law enforcement officials use progressive positivism instruments, such as restorative justice as a method of legal resolution.